Hop fields in crop rotation - Darja KOCJAN AČKO (Acta Agriculturae Slovenica, 2010)
A number of factors influenced the increased number of crops on Slovenian farms legal limitation of maize production to two years on the same field, introduction of integrated crop production and certain measures of the Slovene Agri-Environmental Programme. Crop rotation on hop fields that has already been analyzed on 22 hop growing and livestock farms in Spodnja Savinjska dolina in 2008 show that the maize monoculture has been supplemented by some other crops like wheat, barley, lucerne, clover-grass mixtures and high beans; compared to the conventional production in the past, the crop rotation is now longer. Phytosanitary adequacy of two- and three-year rotation could be improved with supplementary crops, that is with fodder crucifers (fodder rapeseed and rape, forage kale), green manure (white mustard, oil radish), legume crops (soya, peas, vetch, field bean, white lupin, crimson clover, Persian clover, Egyptian clover) and compound fodders like Landsberger mixture and mixtures of vetch with oat or barley. Prohibition to sow broad-leafed plants in the quarantine rotation due to hop wilting limits the selection of crops to grasses (Italian rye-grass) and fodder grains (maize, barley), but the farmers could increase the selection of grains with oats, rye, triticale, mixture of wheat and rye, millet, sorghum and Sudan grass. With the use of recommended crop rotations in two-, three- and four-year rotation, we can expect the increased influence of crop rotation on improved health condition of the new hop plantations in the future with simultaneous reduction of the use of pesticides as well.